Aliran Pencak Silat Sang Maung Bodas: Nilai Filosofis, Historis, dan Kultural dalam Tradisi Pesantren dan Warisan Pajajaran - Robi Robi; Siti Robiah Sopaniah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to explore the philosophical, historical, and cultural values within the Sang Maung Bodas martial art school as a representation of Sundanese heritage and pesantren spiritual tradition. Using a qualitative descriptive approach through literature study, participatory observation, and interviews with martial arts masters and pesantren leaders, the study reveals that Sang Maung Bodas functions not only as self-defense but also as a character education system combining spiritual, physical, and social aspects. Values such as sincerity, loyalty, and moral responsibility serve as the foundation for students’ and warriors’ character formation. This martial art embodies the continuity between Pajajaran’s noble teachings and Islamic values within pesantren education. Therefore, Sang Maung Bodas holds strategic relevance for modern education emphasizing balance among body, soul, and moral virtue.